Circadian rhythms in ischaemic heart disease: key aspects for preclinical and translational research: position paper of the ESC working group on cellular biology of the heart . Issue 12 (10th September 2021) - Lecour, Sandrine; Du Pré, Bastiaan C; Bøtker, Hans Erik; Brundel, Bianca J J M; Daiber, Andreas; Davidson, Sean M; Ferdinandy, Peter; Girao, Henrique; Gollmann-Tepeköylü, Can; Gyöngyösi, Mariann; Hausenloy, Derek J; Madonna, Rosalinda; et al.
Abstract: Circadian rhythms are internal regulatory processes controlled by molecular clocks present in essentially every mammalian organ that temporally regulate major physiological functions. In the cardiovascular system, the circadian clock governs heart rate, blood pressure, cardiac metabolism, contractility, and coagulation. Recent experimental and clinical studies highlight the possible importance of circadian rhythms in the pathophysiology, outcome, or treatment success of cardiovascular disease, including ischaemic heart disease. Disturbances in circadian rhythms are associated with increased cardiovascular risk and worsen outcome. Therefore, it is important to consider circadian rhythms as a key research parameter to better understand cardiac physiology/pathology, and to improve the chances of translation and efficacy of cardiac therapies, including those for ischaemic heart disease. The aim of this Position Paper by the European Society of Cardiology Working Group Cellular Biology of the Heart is to highlight key aspects of circadian rhythms to consider for improvement of preclinical and translational studies related to ischaemic heart disease and cardioprotection. Applying these considerations to future studies may increase the potential for better translation of new treatments into successful clinical outcomes. Graphical Abstract: